Отбасы алғашқы-әлеуметтік институттың негізі - Есекешова, М.Д.; Ташкенбаева, Ж.М. (My University, 2013)
Family and school is the very important teaching institute, which works for the development of child. A family is the most important in the man life. The character of a person is formed, created in the family.